Idhâfah Al-Murfimat Al-Indûnîsiyyah Ila Al-Muhadatsah Bi Al-Lughah Al-‘Arabiyyah Lada Thalibat Al-I’dad Al-Lughawiy Bi Jami’ah Ar-Raayah - Alvira Ulfa; Fahmi Ridha (Ukazh: Journal of Arabic Studies, 2021)
هدفت هذه الدراسة الحالية إلى جمع المورفيمات الإندونيسية المضافة إلى المحادثة باللغة العربية لدى طالبات الإعداد اللغوي بجامعة الراية وتصنيفها، والتنبيه عليها والإرشاد إلى تصويبها، ومعرفة أهم الأسباب التي أدت إلى شيوع هذا الكم المزعج من الألحان في لغة الضاد، ومن ثم تقديم الطرق المقترحة المناسبة لها. وسلكت الباحثة في هذا البحث المدخل الكيفي من بحث وصفي تحليلي على منهج دراسة الحالة. وقامت الباحثة بجمع البيانات باستخدام طريقة المقابلة، والملاحظة، والدراسة الوثائقية. وأثبتت النتائج من هذه الدراسة وجود المورفيمات المضافة إلى المحادثة باللغة العربية لدى طالبات الإعداد اللغوي بجامعة الراية. وأما العوامل المؤدية إلى تلك الظواهر هي تأثير اللغة الأم في اللغة الثانية (العربية)، وعدم وجود مقابلة بعض المفردات الإندونيسية في اللغة العربية. وطرق علاج هذه الأخطاء هي: فرض الطالبات بتقليد النغمة وموسيقى الكلام العربي، وحفظ أساليب كلام العرب، وتوفير المشرفين والموجهين للأنشطة اللغوية. The aim of this study was to collecting Indonesian morphologies added to Arabic conversation made by the students of the Language Preparation Program at Al-Raayah Collage and classifying them, alerting them and guiding to correct them, and knowing the most important reasons that led to the prevalence of this disturbing amount of errors in "the language of the dad", then presenting the proposed methods appropriate to it. The researcher used the qualitative approach from a descriptive and analytical research on the case study approach. The researcher collected the data using the method of listening, speaking, interviewing and documentary study. And the results of this study proved the existence of the morphemes added to the conversation in the Arabic language among students of The Language Preparation Program of Al-Raayah Collage. The factors that lead to these phenomena are the influence of the mother tongue in the second language (Arabic), and the absence of equivalent words of some Indonesian vocabularies in Arabic language. And the ways to overcome these errors are: imposing female students by imitating the tone and music of Arabic speech, preserving the methods of the Arabs’ speech, and providing supervisors and mentors for language activities.